Transcriptome analysis of the regenerating tail vs. the scarring limb in lizard reveals pathways leading to successful vs. unsuccessful organ regeneration in amniotes. Issue 2 (February 2017) - Vitulo, Nicola; Dalla Valle, Luisa; Skobo, Tatjana; Valle, Giorgio; Alibardi, Lorenzo
Abstract : Background : Lizards are amniotes regenerating the tail but not the limb, and no information on their different gene expression is available.Results : Transcriptomes of regenerating tail and limb blastemas show differences in gene expression between the two organs. In tail blastemal, snoRNAs and Wnt signals appear up‐regulated probably in association with the apical epidermal peg (AEP), an epithelial region that sustains tail regeneration but is absent in the limb. A balance between pro‐oncogenes and tumor suppressors is likely present in tail blastema allowing a regulated proliferation. Small collagens, protease inhibitors, embryonic keratins are up‐regulated in the regenerating tail blastema but not in the limb where Wnt inhibitors, inflammation‐immune and extracellular matrix proteins depress cell growth.Conclusions : The AEP and the spinal cord in the tail maintains Wnt and fibroblast growth signaling that stimulate blastema cell proliferation and growth while these signals are absent in the limb as a consequence of the intense inflammation. Regeneration of amniote appendages requires a control of cell proliferation and inflammatory‐immune reactions to form an apical epidermal cap. Genes that control cell proliferation and inflammation, addressing regeneration and not tumor formation in the tail and scarring in the limb are discussed for future studies. Developmental Dynamics 246:116–134, 2017 . © 2016 Wiley Periodicals, Inc. Key Findings: Lizards are amniotes capable to regenerate the tail but not the limb ‐transcriptomes of the regenerating limb and tail in lizards were compared. 115 key regenerative genes were found. WNT genes lead to tail regeneration. Inflammatory genes lead to limb scarring.